Edukasi Manajemen Stres pada Remaja di Masa Pandemi Covid-19 - Ni Ketut Erawati; Wayan Sugandini; Made Juliani (STIKes Surya Global Yogyakarta, 2023)
Background of study: The Covid-19 pandemic has had a psychological impact on students, especially teenagers. The limited learning activities, the opportunity to meet friends and the limited means of supporting distance learning infrastructure bring their own burdens for students. This is often causes complaints such as anxiety, boredom, wanting to meet friends, worrying about the family's economic condition. Those are some indicators that there has been a stressful condition for students.This usually occurs in teenager students aged 13-14 years, who are still unstable emotionally and not enough yet to facing a problem.The purpose of this study is to increase the knowledge of teenager students about stress management through education.Methods: This research was an experimental type with a one shot case study design and the subject of 30 students.Results: The results showed that the average knowledge of students was 76.3. Hypothesis testing with an independent t-test of one sample showed a significance value of p = 0.026 at p = 0.05, so Ho was rejected and Ha was accepted, it means that the lowest level of student knowledge was 73 (with value = 73).Conclusion: This indicates that education is an important point that needs to be considered, with a good understanding of how to manage stress. It is hoped that the level of stress experienced by students during the Covid-19 pandemic can be reduced.Keywords: Level of knowledge; Education; Stress Management